2011
DOI: 10.1177/0011000011398726
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Personality-Related Career Decision-Making Difficulties

Abstract: This study tests the temporal stability and the concurrent and predictive validity of the Emotional and Personality-related Career decision-making Difficulties (EPCD) model and questionnaire. Five hundred forty-three participants filled out the EPCD twice, 3 years apart. The Anxiety cluster was the most stable of the three, followed by the Self-Concept and Identity cluster, and then the Pessimistic Views cluster, which showed a significant decrease. Participants who reported having made a career decision by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 43 publications
(84 reference statements)
9
59
0
Order By: Relevance
“…Particularly, the correlation coefficients between Time 1 and Time 2 varied across the three dimensions. The dimensions of anxiety and self-concept and identity had higher temporal stability than did pessimistic views, and this result is consistent with the finding of the 3-year follow-up study on the original EPCD (Gati, Asulin-Peretz, & Fisher, 2012). The discrepancy in temporal stability may indicate that pessimistic views reflect one's cognitive view or perspective toward their world of work, which changes with one's experiences, but the other two clusters are associated more with emotional aspects that are intrapsychic and more stably maintained (Gati et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Particularly, the correlation coefficients between Time 1 and Time 2 varied across the three dimensions. The dimensions of anxiety and self-concept and identity had higher temporal stability than did pessimistic views, and this result is consistent with the finding of the 3-year follow-up study on the original EPCD (Gati, Asulin-Peretz, & Fisher, 2012). The discrepancy in temporal stability may indicate that pessimistic views reflect one's cognitive view or perspective toward their world of work, which changes with one's experiences, but the other two clusters are associated more with emotional aspects that are intrapsychic and more stably maintained (Gati et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…For example, it was found that the EPCD was associated with emotional and personality‐related variables, career decision‐making self‐efficacy, and the CDS (Hou et al, 2015; Jin et al, 2015; Saka & Gati, 2007). It was also found that the EPCD showed differential scores for students with different help‐seeking intentions, decidedness, and self‐reported difficulties (Gati, Asulin‐Peretz, & Fisher, 2012; Oztemel, 2013; Saka & Gati, 2007). Longitudinally, the EPCD was found to successfully predict later decidedness and choice confidence (Gati et al, 2012; Saka et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In a longitudinal study with 747 university students in Israel, Saka and Gati (2007) found that EPCD not only had a good structural validity but could specifically capture some stable and enduring components of career decision-making difficulties, given that the students who showed higher level of decision-making difficulties measured by EPCD had less progress and lower choice confidence after a 24-week time period. Finally, in a 3-year follow-up study, Gati, Peretz, and Fisher (2011) found that participants who reported having made a career decision after 3 years scores lower on EPCD at the first administration than did those who remained undecided after 3 years. Furthermore, whereas the decided group showed a decrease in the EPCD scores during the 3-year interval, the undecided group showed no significant decrease.…”
Section: Review Of Career Decision-making Assessmentmentioning
confidence: 92%